Processing of Polypropylene/ Spheri Glass 3000 Nanocomposites by Melt Intercalation Method. (2016) - Daniel, D. Jafrey; Panneerselvam, K.
Abstract: Polymers reinforced with a certain type of nano fillers labelled polymer nanocomposites is become as an area of research among several researchers. Polypropylene (PP) as matrix and Spheri glass 3000 (SG) as reinforcing filler was considered in study. The polymer nanocomposites was prepared by melt intercalation method with help of twin screw extruder. The percentage of SG was varied at four different levels (i.e. 1.25, 2.5, 5, 7.5 wt. %). The PP/SG glass 3000 mixture was processed in twin screw extruder with different zones like conveying zone, melting zone, mixing zone and plasticizing zone which helps in achieving homogenous dispersion of SG in PP. The processing parameters of the extruder were studied and the optimal parameters like screw speed (65 rpm), inlet feed (7 rpm), degassing pressure (40 mm of Hg) and high density cartridge heater (HDCH) temperature profile (180°C-230°C) were selected to obtain PP/SG nanocomposites. The structure formed was studied using X-ray diffraction (XRD) which shows an exfoliated structure and the dispersion studies were carried out using Field Emission Scanning Electron Microscope (FE SEM).